Monetary Policies and European Office Markets Dynamics. Issue 4 (2nd October 2022) - Coën, Alain; Lefebvre, Benoit; Simon, Arnaud
Abstract: The purpose of this paper is to study the consequences of unconventional monetary policies on Europe's commercial real estate market. To investigate the role of money supply on real estate markets dynamics, we use panel modelling. Our main objective is to analyze the relationships between office price indexes and monetary variables. Our panel analysis focuses on price dynamics across 16 main office markets in Europe between 2009 and 2019. We have constructed for each market a monetary index suitable for commercial real estate. Our robust results, corrected for the presence of errors-in-variables, report that a positive relationship exists between the global money supply and office prices. Moreover, the largest markets seem more affected by the massive injections of liquidity from the central banks, especially those from the European Central Bank (ECB). We highlight significant differences among office markets in Europe.